(untitled) (REMUNOM, 2024)
Artificial Intelligence processes and stores an unimaginable amount of information and is already being used to assist professionals in various professions, helping them perform tasks, answer questions and provide useful information, improving the efficiency and productivity of employees, allowing them to perform tasks more quickly and accurately. In a country like Brazil, where private economic activity is oppressed and discouraged, both for bureaucratic reasons and tax burdens, a country that suffers from economic crises, legal uncertainty and a profusion of legislation being created all the time, as well as changes in understandings in higher courts routinely, which the common man is unable to keep up with, AI is already being a great help in making business decisions and calculating the risk of economic activity. The development of AI is already providing services for other companies to improve their management, especially in risk management, very important for entrepreneurs and administrators who have set up their businesses in countries with extremely unstable and volatile markets. For example, the ALADDIN software developed by the fund manager BlackRock accumulates information and data, managing such information to the point of providing users with greater risk management and, consequently, more assertive decision-making, improving the chances of the business surviving and developing. Tools like this can improve the quality of administrative management and forecasting of Brazilian entrepreneurs, reducing the bankruptcy rate.